A project feasibility study for South Road a garment shop operation - Mahinay, Naomi B.
The feasibility study was conducted to test the viability of establishing shop operation. To determine whether the business will be productive, profitable or to be pursued. The study also investigated the possibility if the proposed project may be operational within two years. Personal interviews were made on randomly selected female residents of the proposed vicinity and people vicinity and people having their own existing garment business. Researches were done on the different government agencies supporting this type of livelihood program. Results show that the proposed garment shop is feasible.